Stage Embodiment of Karakalpak Folklore: A Cultural Exploration through Theatrical Expression - Saparov Rinat Kuralbayevich (Periodica Journal, 2023)
Karakalpak folklore, a rich tapestry of traditions, myths, and legends, has been an integral part of the Karakalpak culture for centuries. In recent years, there has been a growing interest in the representation of this folklore on stage, allowing it to transcend its traditional roots and reach broader audiences. This article delves into the phenomenon of stage embodiment of Karakalpak folklore, exploring its significance in preserving cultural heritage, its impact on contemporary theatrical expression, and its potential implications for cultural identity in a rapidly evolving world.
Keywords: Karakalpak folklore; stage embodiment; theater